Foreword - Rava, Valeria; Volpi, Sonia (Acta Biomedica Atenei Parmensis, 2014)
In previous clinical trials, inhaled hypertonic saline solution was shown to improve lung function and decrease the frequency of exacerbations both in adults and older children with Cystic Fibrosis and is now recommended for individuals older than 6 years with moderate benefit, grade of recommendation B....